Business valuation body of knowledge : - Pratt, Shannon P. (John Wiley & Sons, 2003)
Praise for the First Edition "The beauty of this work is that it points the reader to each professional organization's writings on issues relating to business valuation methodologies and applications. I can't think of an attorney who works with business valuation professionals who should not have this book." -Robert E. Kleeman Jr. CPA/ABV, ASA, CVA, CFE, Clifton Gunderson, LLC "Business Valuation Body of Knowledge will quickly become one of the foremost authoritative sources on the ‘body of knowledge' for business valuations. It is well organized and written in a style which allows it to be used as both a teaching tool and a reference manual." -R. James Alerding CPA/ABV, ASA, CVA, Clifton Gunderson, LLC "When you simply need the answer, Shannon has it for you. The Body is a no-nonsense repository of information!" -Stephen J. Bravo CPA/ABV, CBA, CPF, PFS, Apogee Business Valuations, Inc. "This book is a ‘must have' for every business valuation library. . . . [Shannon has] done an excellent job of compiling a core body of knowledge that is common to all of the major accrediting organizations in the business valuation profession." -Thomas E. Hilton CPA, CVA, Anders, Minkler & Diehl, LLP "The book is great. I especially like the cost of capital chapter. . . . It's one of the few books where there is a succinct description of the different methods to determine the cost of capital. I thoroughly enjoyed reading it and it was a great refresher for me." -Mary McCarter ASA, CFA, Columbia Financial Advisors, Inc.